2022
DOI: 10.3390/ijms23147755
|View full text |Cite
|
Sign up to set email alerts
|

MdMKK9-Mediated the Regulation of Anthocyanin Synthesis in Red-Fleshed Apple in Response to Different Nitrogen Signals

Abstract: The mitogen-activated protein kinase (MAPK) signaling cascade is a widely existing signal transduction system in eukaryotes, and plays an important role in the signal transduction processes of plant cells in response to environmental stress. In this study, we screened MdMKK9, a gene in the MAPK family. This gene is directly related to changes in anthocyanin synthesis in the ‘Daihong’ variety of red-fleshed apple (Malus sieversii f neidzwetzkyana (Dieck) Langenf). MdMKK9 expression was up-regulated in ‘Daihong’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 64 publications
(76 reference statements)
0
6
0
Order By: Relevance
“…After one week of natural drought for 3-week-old A. thaliana (WT and transgenic plants) grown in the same pot, the leaves were taken to extract anthocyanin using 1% ( v / v ) HCl-methanol extraction solution at 4 °C in the dark for 24 h, to determine the anthocyanin content using the pH difference method according to the previous method [ 57 ].…”
Section: Methodsmentioning
confidence: 99%
“…After one week of natural drought for 3-week-old A. thaliana (WT and transgenic plants) grown in the same pot, the leaves were taken to extract anthocyanin using 1% ( v / v ) HCl-methanol extraction solution at 4 °C in the dark for 24 h, to determine the anthocyanin content using the pH difference method according to the previous method [ 57 ].…”
Section: Methodsmentioning
confidence: 99%
“…At the molecular level, studies in apple show a number of candidate genes linking N deficiency to an elevation in the anthocyanin pathway. Low N induces anthocyanin production, partly mediated by the mitogen-activated protein kinase (MAPK) signalling cascade, as shown for red-fleshed apples, where a MAPK family gene, MdMKK9, regulates the N status (Sun et al, 2022). Under low N conditions the autophagy nutrient recycling process can be activated, and studies in apple have demonstrated that the AuTophaGy (ATG) protein, MdATG18a, improves tolerance to nitrogen deficiency via upregulation of the anthocyanin pathway (Sun et al, 2018).…”
Section: Nutrient Stressmentioning
confidence: 99%
“…At the molecular level, studies in apple show a number of candidate genes linking N deficiency to an elevation in the anthocyanin pathway. Low N induces anthocyanin production, partly mediated by the mitogen‐activated protein kinase (MAPK) signalling cascade, as shown for red‐fleshed apples, where a MAPK family gene, MdMKK9 , regulates the N status (Sun et al, 2022). Under low N conditions the autophagy nutrient recycling process can be activated, and studies in apple have demonstrated that the AuTophaGy (ATG) protein, MdATG18a, improves tolerance to nitrogen deficiency via upregulation of the anthocyanin pathway (Sun et al, 2018).…”
Section: The Major Environmental Stress Factors That Affect Fruit Colourmentioning
confidence: 99%